2010
DOI: 10.1103/physrevb.81.115438
|View full text |Cite
|
Sign up to set email alerts
|

Heating and cooling mechanisms in single-molecule junctions

Abstract: In this work we analyze the role played by molecular resonances on the thermal behavior of single molecule junction. We consider a fullerene molecule on a Cu͑110͒ substrate when current is driven across using an scanning tunnel microscope tip. Calculations based on density-functional theory and nonequilibrium Green's functions have predicted a lowering of molecular temperature whenever a resonance gets close to the injection window. This behavior, due on the interplay of emission and absorption phonon processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 15 publications
4
52
0
Order By: Relevance
“…We have also observed that nonequilibrium vibrational occupations for high-energy modes can be cooled down in an intermediate bias regime, which may be understood in terms of a resonant state in the device region. This observation agrees well with resonant cooling reported in other first-principle calculations 63 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We have also observed that nonequilibrium vibrational occupations for high-energy modes can be cooled down in an intermediate bias regime, which may be understood in terms of a resonant state in the device region. This observation agrees well with resonant cooling reported in other first-principle calculations 63 .…”
Section: Discussionsupporting
confidence: 93%
“…One can hint at a qualitative explanation for this cooling behavior examining the local density of states in the device region, as recently reported in Ref. 63 . As observed in Fig.14-(a), there is one resonant peak located at a energy higher than µ eq , which is the common Fermi level before the bias is applied.…”
Section: A Cumulene-benzene-cumulene Junctionsupporting
confidence: 71%
“…Photons can be localized inside a cavity [4][5][6]. In both cases, the bosonic degrees of freedom can be driven into highly excited nonequilibrium states [7][8][9][10][11][12][13][14]. It is challenging to understand these states, because they cannot be described via a Bose-Einstein distribution function.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these states determine the functionality and efficiency of many devices that may be used for nanoelectronic applications [8][9][10][15][16][17][18][19][20][21][22][23], quantum information processing [16,[24][25][26], solar energy conversion [27][28][29][30] or the control of chemical processes [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The measurement correction can be better than the zero-point-motion uncertainty. In addition, vibrational junctions have abundant physical applications such as heat transfer and cooling based on nonequilibrium hot electron transport [13,14], subresonance inelastic electronic transport that is analogous to atomic laser-induced cooling [14,15] and tip-induced cooling [16]. The effective temperature of the molecular island is defined as the internal energy stored in the vibrational degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%